Platonic Eros, Ottonian Numinour and Spiritual Longing in Otaku Culture - Barkman, Adam (Marburg journal of religion, 2010)
Less than a month ago I was in North Korea seeing the sights and engaging in some general research into the philosophical mood of its people. After exploring the desolate, zombie-like town of Kaesong, I happened upon a small shop selling such things as the North’s own brand of Coca-Cola, stamps with Kim Jung Il’s face on them, a myriad of different types of Chinese medicine and, of all things, a manhwa - the Korean name for manga - containing some of the most impressive art I had ever seen; indeed, to my utter surprise, the images in the North Korean manhwa filled me with a deep yearning for something quite inexplicable. Naturally, as a professor of philosophy, I felt obliged to investigate this phenomenon further. And as I did so, I started to realize that certain manga and anime - arguably, the two most sacred objects of otaku culture - have been stirring in me these kinds of feelings ever since I could remember. As a result of this, I immediately came to see that it did not matter whether the culture producing the anime and manga was largely atheistic, like North Korea, Shinto-Buddhist, like Japan, or Christian, like the USA: otaku culture produced anywhere and by any type of believer or nonbeliever seemed to be capable of awakening in me what Plato calls eros and Rudolph Otto calls the numinous. As I moved beyond my own personal reflections to see what scholars of otaku culture have already written on this subject, I found some precedent for my own ideas in the work of Teri Silvio, who has examined the relationship between religious icons and character toys in Taiwan, i Hiroshi Yamanaka, who has discussed “pop cultural spirituality” in the work of Hayao Miyazaki, ii and Susan Napier, who, influenced by Roger Aden’s book Popular Stories and Promised Land: Fan Cultures and Symbolic Pilgrimages, has written about western otaku making “pilgrimages to Akihabara” and has wisely labelled certain anime and manga chatrooms “sacred spaces.” iii Nevertheless, while I agreed with the insights of all these scholars, I felt they did not go far enough in linking their observations to larger philosophical issues. Thus, in this paper I would like to explore the idea of spiritual longing in otaku culture, firstly, by elucidating Plato’s eros and Otto’s numinous, and then, secondly, by examining a few examples from anime and manga which have instilled in me, or others I know, a deep desire for something that can only be described as mysterious, irreducible and spiritual.